Telaah Pemikiran Quraish Shihab dengan Tafsir Al-Misbah pada Surat Ali-Imran Ayat 35-37 Tentang Konsep Pendidikan Anak Perempuan - Yolanda, Yolanda; Razzaq, Abdur; Imron, Kristina (Jurnal Ilmiah Global Education, 2024)
This research aims to determine the concept of girls' education in the Al-Qur'an Surah Ali Imran verses 35-37 in Tafsir Al-Misbah by Quraish Shihab. This research uses a literature review (Library Research). The researcher conducted a study of Quraish Shihab's thoughts or ideas contained in his book Tafsir Al Misbah which was then linked to Surah Ali Imran verses 35-37 which relate to the concept of girls education. There are two sources of data in this research, namely the primary source is data obtained directly from the original source, in this research the primary sources are the Al-Qur'an and the Book of Tafsir Al Misbah by Quraish Shihab. Secondary sources are data that are not directly related to the original source and aim to complement primary data. In this data the author uses interpretive books written by Indonesian figures as well as from journals related to the theme. Researchers will use library techniques to obtain data in this research. The results of this research, namely in Tafsir Al-Misbah, Quraish Shihab outlines his views on girls' education based on Surah Ali 'Imran verses 35-37. He explained that 'Imran's family is an example of how to educate children so that they become righteous and pious descendants. This can be achieved by imitating the Prophet in family matters, praying for children, and emphasizing the importance of education that fosters obedience to Allah. Quraish Shihab emphasized that the right to education must be given to girls equally as to boys. The right environment is also very important in the child's growth and development process. Apart from religious education, attention to social education is also necessary to equip children to interact with society.